Inibição enzimática analisada com uma abordagem da mecânica estatística - Freire, Thales Souza (2019)
In the conventional approach of Biochemistry, a parameter for the description of the functioning of an enzyme is the rate of conversion of substrate into product in the presence or absence of an inhibitor. Given this consideration, the aim of this work was to study the enzyme kinetics from Statistical Mechanics point of view. So, starting from an approximation to the thermodynamic equilibrium, it was possible to use the grand canonical ensemble to get equations for the rate of product formation in reactions catalyzed by homodimeric enzymes. It was considered the situation where there could be at least two possible conformations for each monomer, thus enabling modeling of the positive and negative cooperative effects based on the energies of the system micro-states. These equations were used to obtain a reaction rate curve as a function of the concentrations of the substrate and the inhibitor. In these simulations were obtained the expected sigmoid shaped curve for the enzymes of this type and the model was applied to a special situation where an inhibitor causes enzymatic activation. Then, equations for 50% reduction in the reaction rate were deduced, where non-linear curves were obtained as a function of substrate concentration, allowing to identify positive and negative cooperativity. Finally, the method was generalized for enzymes with more than two binding sites and tested in a real case, giving a good fitting of the experimental data.